Sectoral Employment Effects of Economic Downturns - Neil Foster-McGregor; Doris Hanzl-Weiss; Sandra M. Leitner; Sebastian Leitner; Nirina Rabemiafara; Fadila Sanoussi; Robert Stehrer; Terry Ward (The Vienna Institute for International Economic Studies (wiiw), 2012)
The recent economic downturn The decline in GDP during the recession has been concentrated in manufacturing and construction and triggered significant (though smaller) declines in basic services (distribution, hotels and restaurants, and transport). The decline in manufacturing production was particularly strong in Germany, while in Spain and Ireland as well as the Baltic states there was a pronounced decline in construction, which had expanded markedly in these countries over the years preceding the recession. Just as in previous economic downturns in the EU, the recent recession has hit investment goods industries (including construction) much harder than consumer goods industries, essentially because investment can be postponed in a way that consumption cannot; nevertheless, within the latter, the production of durable goods – which are similar to investment goods in this respect – was hit hard as well. The effect on employment of the downturn differed markedly among sectors and countries according to the strength of the measures adopted both by employers and governments to preserve jobs, but also according to expectations about the pace and scale of recovery and the sustainability of the previous pattern of growth. Although average hours worked declined significantly in manufacturing during the worst period of the recession in 2009, supported by measures to preserve jobs in many countries, since then there has been a widespread increase, reflecting the reluctance of employers to take on workers in the context of a hesitant recovery and the uncertainty of longer-term prospects. Just as the recession disproportionately affected industry, so too the recovery was in its initial stages stimulated by an upturn in manufacturing as demand for investment and durable goods picked up. This was especially the case for chemicals and motor vehicles where output began to recover strongly in the latter part of 2009 and during 2010. Value-added in industry grew by 6% between 2009 and 2010 in the EU as a whole, considerably more than in other parts of the economy (in construction, value-added continued to decline). In those sectors where most efforts have been made to preserve jobs – in the engineering industries and motor vehicles in particular – labour productivity at the beginning of 2011 was below the level before the onset of recession in a number of countries. This could dampen the rate of job creation as and when recovery takes place since it implies that output could be increased without any immediate need to expand employment. Employment trends in selected sectors results from analysis of long-term developments Employment is strongly related to changes in value-added, though an increase in value-added tends to be partly met by productivity growth as well as by employing more people. Similarly, a fall in value-added tends to be associated with a decline in productivity growth as well as a decline in employment, though lags in adjustment may delay the latter. The relationship between employment and real wages tends to be significant in manufacturing, where increases in real wages tend to reduce the growth of employment; this is not the case in services. In the UK, as in the US, real wages tend to adjust more quickly to changes in labour demand than in Germany and France, suggesting that labour markets are more flexible in the former countries. There is an inverse relationship between average hours worked and the number employed, indicating in general that the more hours people work, the smaller the number employed and vice versa, so that adjustments in working time has an important effect on jobs. Investment in ICT has positive and significant effects on employment in manufacturing, probably working through improvements in productivity. The opposite is the case in services, suggesting that the increasing use of ICT tends to reduce employment. After a shock, it takes up to three years for employment to return to trend levels in France, Spain, Belgium and the Netherlands. In the other countries, the pace of adjustment is faster, at only one-and-a-half to two years on average. Changes in the composition of employment Over the recession period from 2007 to 2010, the share of jobs filled by women continued to increase across the EU. This, however, reflects the large job losses in manufacturing and construction where few women are employed. In most sectors, even in services, the share of jobs filled by women declined. The share of jobs filled by workers aged 55 and over has increased in most parts of the EU over the past ten years, reflecting a tendency for older people to remain longer in work. This continued to be the case over the recession period, unlike during previous periods of economic downturn when early retirement has been a major means of reducing work forces. The main group hit by the present crisis are the young below the age of 25. The proportion of the work force with tertiary education increased in all sectors over the years leading up to the recession; the same is true for the share of employment accounted for by managers and professionals. Both trends have continued over the recession period. There has been a shift from full-time to part-time jobs over the recession period, which may reflect uncertainty among employers over future prospects as well as the pursuit of more flexible organization of work. Employment experience in previous economic downturns There are some differences between previous periods of downturn in those sectors in which employment was most affected. In all periods, however, employment continued to expand in business services and hotels and restaurants. Economic crises were predominantly weathered by adjustments in hours worked to preserve jobs and the know-how of the work force, thus limiting the costs of re-employment and training. This tendency was strongest in the 1970s, moderate in the 1980s and mixed in the 1990s. Value-added was generally more volatile than the number employed and hours worked. During the three periods of economic downturn, value-added grew only in business services. The largest losses were observed in machinery and equipment, basic metals and construction in all three periods. Sectoral interdependencies For each job created by an increase in final demand in a particular sector, there are between 1.4 and 2.3 additional jobs created in the economy as a whole. Employment multipliers are highest in manufacturing (especially in chemicals, electrical equipment and transport equipment) and are lowest in services, which need fewer inputs from other sectors. Domestic employment multipliers tend to have remained broadly unchanged over the past 15 years or so whereas international employment multipliers (the effect of growth in one country on employment in others) have increased markedly, reflecting the growing importance of production networks and international integration. Employment creation in services is mainly a domestic process, whereas within manufacturing, job creation takes place internationally (particularly in textiles, chemicals and electrical equipment and transport equipment). Growth of demand in the EU tends to lead to significant employment creation in other countries, reflecting the increase in imports that it results in. This is particularly so with respect to electrical equipment, textiles and chemicals, though it is also the case for each of those that growth of demand increases employment not only in the Member State in which it occurs but also in other parts of the EU. Measures taken to support employment during the crisis Measures to counter the effect of the recession on employment were implemented in all Member States. However, those were mainly general; relatively few responses were sector-specific, such as car scrapping schemes, which were introduced in a number of countries, and cuts in value-added tax on hotels and restaurants (in Ireland and France). But there has been a decentralization of pay bargaining to company level in some sectors in some countries (such as in basic metals or chemicals in Germany). Many countries introduced expansionary fiscal policies to stimulate demand as well as short-time working arrangements (mainly concentrated in manufacturing). In a number of countries, there has been an expansion of training and work experience programmes, recruitment incentive schemes for employers hiring new workers, support to business start-ups, measures to increase access to credit, pay freezes and more flexible working arrangements, all designed to increase employment. Young people, who have been severely affected by the recession and the lack of job creation, have been a particular target for government support, in the form of subsidized employment schemes, work placement programmes, work experience or training guarantees and intensified job search assistance.
Keywords: E24; J08; J21; J23; 330; employment effects of crisis; sectoral employment; economic downturns and sectoral labour demand; policy reactions